Nutritional and Sensory Quality and Heavy Metal Contents of Commercial Pork Products in West Bengal - Chowdhury, J.; Chakraborty, R.; Biswas, S.; Sahoo, S.; Das, S.K. (Journal of Meat Science, 2015)
A study was conducted to evaluate proximate composition, fatty acids and energy contents, heavy metal contents and consumer acceptance of ham, salami, sausages and nuggets produced at meat plant (bacon factory), Haringhata Farm, West Bengal. The mean of moisture (56.47 ± 0.150 to 64.70 ± 0.159), protein (16.23 ± 0.147 to 26.91 ± 0.145 ), total lipids (8.91 ± 0.129 to 18.87 ± 0.097) , mono unsaturated fatty acids (MUFA) (4.07 ± 0.028 to 8.87 ± 0.026), poly unsaturated fatty acids (PUFA) (0.95 ± 0.013 to 2.31 ± 0.027), saturated fatty acids (SFA) (3.04 ± 0.011to 6.83 ± 0.012), cholesterol (47.24 ± 0.128 to 62.11 ± 0.148) and energy content (191.60 ± 2.02 to 254.20 ± 2.01) were recorded. Heavy metal contents like copper (Cu) (0.74 ± 0.008 to 0.97 ± 0.009) and zinc (Zn) (5.59 ± 0.068 to 12.70 ± 0.132) were also recorded. Lead (Pb), arsenic (As) and tin (Sn) contents were at below detectable level (BDL). Proximate compositions were significantly (p<0.05) different among all products. Significant difference (p<0.05) has been observed for MUFA and PUFA in all products excepting in between ham and nuggets. SFA was significantly different (p>0.05) among all the products. Whereas cholesterol content did not differ significantly in between salami and sausages and energy content did not differ significantly in between ham and salami. Products were free from Pb, As and Sn contents. Organoleptic evaluation showed that over all acceptability did not differ significantly (p>0.05) in salami, sausages and nuggets though it differed significantly when compared with ham.